Flood hazard assessment and mapping of River Swat using HEC-RAS 2D model and high-resolution 12-m TanDEM-X DEM (WorldDEM) - Farooq, Muhammad; Shafique, Muhammad; Khattak, Muhammad Shahzad (Natural hazards (Dordrecht), 2019)
Floods are among the most devastating and recurring natural hazards and have caused extensive economic losses to human lives and infrastructures around the world. Swat valley in northern Pakistan is prone to frequent floods and was severely affected by the Flood2010 in the recent past. Flood hazard assessment is a non-structural strategy for flood mitigation in addition to the structure measure. In this study, 60 km long reach of the River Swat (Khwazakhela Bridge–Chakdara Bridge) was modeled using the HEC-RAS 2D model and high-resolution 12-m WorldDEM. The model was calibrated and validated for only historical maximum flood event, i.e., Flood2010 using Manning’s ‘n’ values, flood stage at the Chakdara Bridge and satellite imagery-based Flood2010-observed extent. In addition, flood model sensitivity to the DEM was carried out and simulated maximum depth was 12, 13, 14, and 25 m for the 12-m WorldDEM, 30-m SRTM, 30-m ALOS and 30-m ASTER DEMs, respectively. Designed hydrographs were prepared for 2, 5, 10, 25, 50, and 100-year return periods based on the Flood2010-observed hydrograph. Finally, the model was simulated for 2, 5, 10, 25, 50, and 100-year return periods with full momentum equation as the calculation method. Simulated extents based on the 12-m WorldDEM were used for the preparation of flood hazard maps. Landcover exposure to the designed flood events shows that agriculture including orchards is the major potential affected class with affected areas up to 55 Km 2 . The developed flood hazard maps will enable the policy makers to mainstream flood hazard assessment in the planning and development process for mitigating flood hazard in Swat Valley.